Environmental integration in maritime education: A holistic approach - Marudut Bernadtua Simanjuntak; Irma Rasita Gloria Barus (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
This research investigates the integration of environmental science education within maritime curricula at the Maritime Institute Jakarta. Focusing on 70 cadets across Nautical, Technical, and Port and Shipping Management majors, a qualitative descriptive approach is employed. Results reveal varying levels of environmental awareness, integration perception, and challenges. Nautical Major demonstrates high awareness and positivity but faces time constraints. Technical Major shows a mixed perception with resistance to change. Port and Shipping Management Major lags behind, identifying a lack of clear guidelines. The research aligns with theoretical frameworks, emphasising tailored approaches to curriculum development. Implications include curriculum adjustments, targeted interventions, and strategic communication. The results contribute to the goal of producing "eco-navigators" – maritime professionals adept at both technical proficiency and environmental consciousness. As the maritime industry navigates sustainability challenges, this research provides valuable insights for refining environmental science education, fostering a new generation of maritime professionals aligned with global sustainability imperatives.